PERANCANGAN INFRASTRUKTUR TEKNOLOGI INFORMASI MENGGUNAKAN KERANGKA KERJA TOGAF PADA PEMERINTAH DAERAH LAMPUNG UTARA - Elvia Fajarwati (IIB Darmajaya, 2016)
In accordance with Indonesian Presidential Instruction No. 3 of 2003 on Policy National Strategy for Development of E-Government. In order to realize the implementation of a strong bureaucracy, professional, effective, productive in providing excellent service to the community is one of the objectives of good governance at the local government, especially in North Lampung Local Government. To achieve these goals, it is necessary to develop systems of management and work process and utilize services that use information and communication technology (ICT) is appropriate. Information technology infrastructure is a foundation that will support the entire information system which will provide IT services to the organization, so it needs an infrastructure planning. TOGAF (The Open Group Architecture Framework) is a framework that will be used as reference in designing the information technology infrastructure in North Lampung Local Government. The results of this study are: (1) From the result of design using TOGAF ADM candidate obtained 28 new applications are proposed to be developed in North Lampung Local Government. (2) Generate a fiber optic connection to the rest of SKPD connected to the metro-LAN or Metro Area Network (MAN). (3) Generate the concept of